A Review on Micro-Watts All-Digital Frequency Synthesizers - Venkadasamy Navaneethan; Boon Chiat Terence Teo; Annamalai Arasu Muthukumaraswamy; Xian Yang Lim; Liter Siek (Micromachines)
This paper reviews recent developments in highly integrated all-digital frequency synthesizers suitable to deploy in low-power internet-of-things (IoT) applications. This review sets low power consumption as a key criterion for exploring the all-digital frequency synthesizer implemented in CMOS fabrication technology. The alignment with mainstream CMOS technology offers high-density, comprehensive, robust signal processing capability, making it very suitable for all-digital phase-locked loops to harvest that capacity, and it becomes inevitable. This review includes various divider-less low-power frequency synthesizers, including all-digital phase-locked loops (ADPLL), all-digital frequency-locked loops (ADFLL), and hybrid PLLs. This paper also discusses the latest architectural developments for ADPLLs to lead to low-power implementation, such as DTC-assisted TDC, embedded TDC, and various levels of hybridization in ADPLLs.